Navigating a Minefield: Meta-Synthesis of Teen Mothers' Breastfeeding Experience. Issue 3 (May 2020) - SmithBattle, Lee; Phengnum, Wisitsri; Punsuwun, Sasinun
Abstract : Abstract: Teen mothers have lower rates of breastfeeding duration and exclusivity than older mothers. A growing body of qualitative research on teen mothers' experience helps to explain these disparities. Following a systematic search to identify relevant research, we synthesized the findings from 22 primary studies to conclude that teen mothers navigate a minefield that undermines their intention to breastfeed and their breastfeeding confidence and skill. This metaphorical minefield reflects competing norms for infant feeding and good mothering, as evident in mixed support from teens' social networks; fragmented and stigmatizing healthcare; and spaces that are inhospitable to teen mothers and breastfeeding mothers in general. In recognition of this minefield, we urge clinicians to: respect teen mothers' infant feeding decisions; develop collaborative relationships based on the principles of patient-centered and strength-based care; challenge stigmatizing healthcare practices; welcome teen mothers and their significant others to clinical settings; and press health systems to fully implement probreastfeeding policies. We also recommend further study to extend our knowledge about teen mothers' breastfeeding experiences. Abstract : Dr. Lee SmithBattle, a well-known expert on teen pregnancy, and her colleagues examine breastfeeding among teens in this meta-synthesis. They noted that breastfeeding is deeply meaningful to young mothers, however teens navigate a minefield that undermines breastfeeding intentions and development of skill and confidence. This is often characterized by contested norms and spaces that are inhospitable and stigmatizing to teen mothers. Nurses can use these data to support and encourage teens who are breastfeeding.